mfherbst/look4bas v0.3.0 - Michael F. Herbst (Physics World, 2019)
Features Support for more download formats: Gaussian94 CFOUR (only experimental support) NWChem ORCA pyscf Q-Chem Turbomole (only experimental support) Misc python >= 3.5 is now required